Antimicrobial Susceptibility of Streptococcus suis Isolated from Diseased Pigs in Thailand, 2018–2020 - Kamonwan Lunha; Wiyada Chumpol; Sukuma Samngamnim; Surasak Jiemsup; Pornchalit Assavacheep; Suganya Yongkiettrakul (Antibiotics, 2022)
Streptococcus suis is a porcine and zoonotic pathogen that causes severe systemic infection in humans and pigs. The treatment of S. suis infection relies on antibiotics; however, antimicrobial resistance (AMR) is an urgent global problem, pushing research attention on the surveillance of antibiotic-resistant S. suis to the fore. This study investigated the antimicrobial susceptibility of 246 S. suis strains isolated from diseased pigs in Thailand from 2018–2020. The major sources of S. suis strains were lung and brain tissues. PCR-based serotyping demonstrated that the most abundant serotype was serotype 2 or ½, followed by serotypes 29, 8, 9, and 21. To the best of our knowledge, this is the first report describing the distribution of AMR S. suis serotype 29 in diseased pigs. The antimicrobial susceptibility test was performed to determine the minimum inhibitory concentrations of 35 antimicrobial agents. The results showed that important antimicrobial agents for human use, amoxicillin/clavulanic acid, daptomycin, ertapenem, meropenem, and vancomycin, were the most effective drugs. However, a slight decrease in the number of S. suis strains susceptible to amoxicillin/clavulanic acid and vancomycin raised awareness of the AMR problem in the future. The data indicated a tendency of reduced efficacy of available veterinary medicines, including ampicillin, cefepime, cefotaxime, ceftiofur, ceftriaxone, chloramphenicol, florfenicol, gentamicin, penicillin, and tiamulin, for the treatment of S. suis infection, thus emphasizing the importance of the prudent use of antibiotics. The widespread of multidrug-resistant S. suis strains was identified in all serotypes and from different time periods and different regions of the country, confirming the emergence of the AMR problem in the diseased pig-isolated S. suis population.